2010
DOI: 10.2214/ajr.09.3779
|View full text |Cite
|
Sign up to set email alerts
|

Extracolonic Findings on CT Colonography Increases Yield of Colorectal Cancer Screening

Abstract: CTC increased the odds of identifying high-risk lesions by 78%. CTC should be considered as an alternative to optical colonoscopy for colorectal cancer screening or as a onetime procedure to identify significant treatable intracolonic and extracolonic lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 26 publications
6
42
2
Order By: Relevance
“…In common with researchers working in an asymptomatic setting, we found that the highest categories (E3, E4) were least frequently reported: a US screening study of 2277 patients found that 46% had at least one extracolonic finding, but this was rated as E3 or E4 in only 250 patients (11%). 43 The combined rate for E3 and E4 detections in our study was higher (21%), likely reflecting the symptomatic nature and greater age of our cohort.…”
Section: Extracolonic Findingsmentioning
confidence: 51%
See 1 more Smart Citation
“…In common with researchers working in an asymptomatic setting, we found that the highest categories (E3, E4) were least frequently reported: a US screening study of 2277 patients found that 46% had at least one extracolonic finding, but this was rated as E3 or E4 in only 250 patients (11%). 43 The combined rate for E3 and E4 detections in our study was higher (21%), likely reflecting the symptomatic nature and greater age of our cohort.…”
Section: Extracolonic Findingsmentioning
confidence: 51%
“…In addition, the largest studies have been performed in asymptomatic individuals being screened for CRC. 42,43 Until now there has been no prospective, randomised study examining the consequences of detecting extracolonic lesions in symptomatic patients having CTC. We collected data on the frequency and nature of extracolonic pathology detected at CTC, subsequent investigations and resource use and ultimate clinical outcome.…”
Section: Introductionmentioning
confidence: 99%
“…55 Because CT colonography produces CT images not only of the colon but also of the upper and lower abdomen, there is a chance that incidental extracolonic findings will be detected. The results of 11 CT colonography studies, where lesions outside the colon were mentioned, 37,40,44,47,[56][57][58][59][60][61][62][63] show that the rate of detection of extracolonic lesions in CT colonography ranges from 18 to 98% and that the incidence of lesions with 'high' clinical significance ranged from 2% to 35%. The incidence of clinically significant extracolonic lesions in the asymptomatic, average-risk population is approximately 4.5%.…”
Section: ) Ct Colonographymentioning
confidence: 99%
“…The majority of findings will ultimately prove to be of little or no clinical significance. 12,13 However, in approximately 10% of cases, significant pathology may be identified, such as early cancers of the kidney and ovary as well as abdominal or pelvic lymphadenopathy in underlying lymphoma. Abdominal aortic aneurysms >5 cm in transverse diameter may be detected incidentally.…”
Section: Introductionmentioning
confidence: 99%
“…Abdominal aortic aneurysms >5 cm in transverse diameter may be detected incidentally. 12,13 Visualisation of such pathology is not possible with OC or DCBE. CTC is less invasive, with minimal complications.…”
Section: Introductionmentioning
confidence: 99%